Arkaik Dönem’de Phokaia’nın Lydia ile İlişkileri Üzerine Tespitler / Detections on Phocaea’s Relationship with Lydia in the Archaic Period - Sabri ARICI (Zeliha Gider Büyüközer, 2021)
The study titled “Detections on the Relations of Phocaea with Lydia in the Archaic Period” was prepared in the light of existing archaeological data, ancient and modern sources. The aim of the study is to reveal that Phocaea had relations with Lydia in the Archaic Period. Phocaea was one of the most important cities of Ionia during the Archaic Period. The city shows that it can be important for Lydia both in sea and road trade thanks to its geographical advantages (it is at the north-west end, which is the entrance to the Gulf of Smyrna, its two sheltered harbors and its proximity to the King’s Road connecting to the east). The state of Lydia, whose capital was Sardis, was in frequent wars and various relations with its neighbors, the Cimmerians, Assyrians, Medes and Persians. It had intense relations with the Ionian cities in the west, sometimes friendly and sometimes hostile. Therefore, the relations of Phocaea, an Ionian city, with Lydia constituted the main subject of the study. The main focus of these relations will be the periods of the last Lydian kings, Alyattes and Croesus. The writings of Herodotus about this have guided this issue. In the study, the historical process of Phocaea, its geographical advantages, overseas colonization activities, Lydia-Ionian relations and the cults and archaeological evidence in the city were discussed, and its possible connections with Lydia were tried to be reached. In the study, the historical process of Phocaea, its geographical features, overseas colonization activities, Lydia-Ionian relations, and the cultural and archaeological evidence in the city were discussed and its possible connections with Lydia were tried to be reached. In this context, it will be tried to reach the conclusion by revealing the archaeological evidences that are thought to be effective in Lydia such as the use of early electron coins by Phocaea, the city wall, the cult of Cybele, the lydion found in the city, the tumulus, the rock tomb and the architectural terracotta found in the Temple of Athena.